Basics of qualitative research techniques and procedures for developing grounded theory - Corbin, Juliet M. 1942- (SAGE, 2008)
"The third edition of Basics of Qualitative Research: Techniques and Procedures for Developing Grounded Theory: shows the steps involved in data analysis (from description to grounded theory) and data gathering by means of theoretical sampling; provides activities for thinking, writing, and group discussion that reinforce material presented in the text; and includes real data and practice with qualitative software such as MAXQDAA, as well as student practice exercises."--Jacket